2020
DOI: 10.1093/jxb/eraa213
|View full text |Cite
|
Sign up to set email alerts
|

The tale of caspase homologues and their evolutionary outlook: deciphering programmed cell death in cyanobacteria

Abstract: Programmed cell death (PCD), a genetically orchestrated mechanism of cellular demise, is paradoxically required to support life. As in lower eukaryotes and bacteria, PCD in cyanobacteria is poorly appreciated, despite recent biochemical and molecular evidence that supports its existence. Cyanobacterial PCD is an altruistic reaction to stressful conditions that significantly enhances genetic diversity and inclusive fitness of the population. Recent bioinformatic analysis has revealed an abundance of death-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 124 publications
(164 reference statements)
0
18
0
Order By: Relevance
“…PCD has been described as part of normal plant development, as well as a response to biotic and abiotic stresses ( Jones, 2001 ; Huysmans et al, 2017 ). Despite research on the subroutines operating in plants has grown considerably in the past few years, their classification, and homology to animal system are still under debate ( van Doorn et al, 2011 ; Huysmans et al, 2017 ; Bhattacharjee and Mishra, 2020 ).…”
Section: Nomenclature and Terms Adopted In The Literature To Refer Tomentioning
confidence: 99%
See 1 more Smart Citation
“…PCD has been described as part of normal plant development, as well as a response to biotic and abiotic stresses ( Jones, 2001 ; Huysmans et al, 2017 ). Despite research on the subroutines operating in plants has grown considerably in the past few years, their classification, and homology to animal system are still under debate ( van Doorn et al, 2011 ; Huysmans et al, 2017 ; Bhattacharjee and Mishra, 2020 ).…”
Section: Nomenclature and Terms Adopted In The Literature To Refer Tomentioning
confidence: 99%
“…Nevertheless, the term PCD is the most widely used term to refer to all instances of RCD, and is often used interchangeably with apoptosis ( Franklin et al, 2006 ; Bidle, 2015 ; Hu and Rzymski, 2019 ; Bhattacharjee and Mishra, 2020 ). Notably, the same morphological and biochemical features, in particular cytoplasmic vacuolation, DNA fragmentation, and caspase activity, are claimed to be hallmarks of PCD in some studies ( He et al, 2016 ) while hallmarks of apoptosis in others ( Ding et al, 2012 ; Li et al, 2020 ; Zhou et al, 2020 ).…”
Section: Nomenclature and Terms Adopted In The Literature To Refer Tomentioning
confidence: 99%
“…Furthermore, the presence of TM infers membrane localization of some OCAs, while others devoid of TM are probably cytosolic. The presence of putative cytosolic and membrane-bound true OCAs depicted the possibility of both intrinsic and extrinsic PCD in cyanobacteria (Bhattacharjee and Mishra, 2020), yet they are poorly appreciated in prokaryotes and require extensive research to validate.…”
Section: Rich Pool Of Cyanobacterial Ocas Having Considerable Diversity and Sharing A Complex Phylogenetic Relationshipmentioning
confidence: 99%
“…Energy components Energy ± σ (kcal mol −1 ) HC (a) RR (b) HC-RR (X) Difference (X-a-b) same strain in different clades may also indicate multiple HGT events (Bhattacharjee and Mishra, 2020). Interestingly, the YN pseudo-variant was only harbored by nitrogenfixing multicellular cyanobacteria, whereas the YS variant…”
Section: S Nomentioning
confidence: 99%
“…Cyanobacterial orthocaspases were believed to prefer caspase substrates ( Berman-Frank et al, 2004 ; Bar-Zeev et al, 2013 ), however, in vitro prokaryotic orthocaspases do not recognize substrates with aspartic acid (D) residue at the P1 position, but instead prefer positively charged R or K residues ( Klemencic et al, 2015 ; Spungin et al, 2019 ). Interestingly, many bacterial orthocaspases contain substitutions in the HC catalytic site; instead of the catalytic dyad, they display a highly variable pair of residues (Y-S, Y-N, Y-C, H-G,-C-Y, Y-R, Y-G, Y-Y, Y-H, Y-Q, or H-P), which presumably renders them proteolytically inactive ( Klemencic et al, 2019 ; Bhattacharjee and Mishra, 2020 ). Analyzing cyanobacterial genomes, it was observed that all cyanobacteria containing orthocaspases contain a proteolytically inactive variant.…”
Section: Introductionmentioning
confidence: 99%